PENGARUH LEVERAGE, MANAJEMEN LABA, DAN STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2008 - 2012 - Fajar Kusworo (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2013)
The purpose of this research was to determine the effect of leverage , earnings management , and ownership structure on firm value in state-owned companies . Based on a population of 18 state-owned companies listed on the Stock Exchange was taken 10 stateowned companies in 2008 to 2012 as the samples in this study according to the criteria of the study , a total of 50 years as a firm observational data . At the stage of data processing are affected data outliers firm by 2 years so the number of samples used in this study for 5 years amounted to 48 firm year . Data analysis was performed using linear regression analysis using SPSS for Windows 16.00. Simultaneous testing results show that leverage , earnings management , government ownership , and public ownership and a significant positive effect on firm value . Result partial test indicates that earnings management does not affect the value of the company , while leverage , government ownership , and public ownership negatively affect the value of the company .